The Performance of Renewable Energy Companies Before and After Initial Public Offering - Ramadhan, Prasetyo (E-Jurnal Akuntansi; Vol 32 No 3 (2022), 2022)
The aim of this research is to analyze the differences in the performance of renewable energy companies before and after the Initial Public Offering (IPO). This research uses Paired Sample T-test as a data analysis method. The population in this study is a renewable energy company that conducts an IPO on the Indonesia Stock Exchange with a total of 3 companies. The sampling technique in this study uses purposive sampling and gets 2 samples. The results of this research indicate that there is no significant difference in the performance of renewable energy companies before and after the IPO. This could be due to the high initial investment costs in the renewable energy industry, the Government's low attention and utilization of renewable energy and the quality of management. Keywords: Renewable Energy Companies; Performance; Initial Public Offering.